Wagon wheels = [Camino de Oregon] - Barton, Charles, 1902-1981; Cunningham, Jack, 1882-1941; Scott, Randolph, 1898-1987; Patrick, Gail, 1911-1980; Grey, Zane, 1872-1939.; Favorite Films Corporation; Paramount Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Paramount Pictures, 1934)
A trail-weary wagon train leader falls for a member of his party traveling with her young son. The romance blooms amidst the dangers and treacherous conditions the wagon train endures as it rolls west.
Originally released as a motion picture in 1934.
Based on: Fighting caravans / Zane Grey.
Randolph Scott, Gail Patrick, Billie Lee, Monte Blue, Raymond Hatton, Olin Howland, Jan Duggan, Leila Bennett.
Cinematographer, William C. Mellor; editor, Jack Dennis; music, John Leipold.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Wagon trains -- United States -- Drama; Indians -- Warfare -- Drama; Overland journeys to the Pacific -- Drama; Western films; Film adaptations; Feature films; Internet videos; Streaming video